The Pragmatic functions of bikago in Japanese honorific speech: Evidence from the drama Asa ga Kita - Elisa Carolina Marion; Angelina Jane Setiawati (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2026)
This study investigates bikago, a type of keigo or honorific form in Japanese, as represented in the historical drama Asa ga Kita. The primary aim is to analyze the use of bikago in relation to the five communicative elements proposed by Kabaya: interpersonal relationships (ningen kankei), place (ba), feelings (kimochi), content (nakami), and delivery form (katachi). Drama Asa ga Kita narrates the story of a tomboyish young woman who enter the male dominated business world during a time of significant social change in Meiji period. This study employs a descriptive qualitative approach, applying thematic analysis to selected dialogues. The findings reveal that bikago frequently appears in contexts with ba levels of 0 or +1, exerting particular influence on the nakami element of communication. Moreover, while some words retain their meaning without bikago, others require the prefixes o- or go- to be meaningful and appropriately interpreted. The results further demonstrate that these prefixes function not only morphologically but also pragmatically, serving as strategies to mark politeness, convey emotion, and construct social identity. Datas from the drama illustrate how bikago is strategically employed across different interpersonal relationships, settings, and communicative purposes, thereby reflecting the cultural expectations of the Meiji period. Theoretically, this study contributes to Japanese pragmatics by situating bikago within broader discussions of identity, gender, and social status. Practically, the findings highlight the importance of incorporating bikago into Japanese language pedagogy to enhance learners’ pragmatic competence and cultural awareness.